National representation in the anaesthesia literature: a bibliometric analysis of highly cited anaesthesia journals - Bould, M. D.; Boet, S.; Riem, N.; Kasanda, C.; Sossou, A.; Bruppacher, H. R. (Anaesthesia, 2010)
Summary While previous studies have investigated the country of origin of anaesthetic publications, they have generally used a medline computer search to identify original articles and have often excluded non‐English language articles. We undertook a hand‐search of journals in the Journal Citation Reports® using the subject category of Anesthesiology. We quantified the number of original articles, editorials, review articles, case reports and correspondence attributed to each country. We also calculated the proportion of articles of each type from countries of each national income category. We analysed 9684 articles published in 2007 and 2008. The United States published more original articles than any other country. High‐income countries published 89.2% of original articles, middle‐income countries 10.5%, and low‐income countries just 0.3%. There were more articles published by middle‐income countries during the study period than a decade earlier, notably from Turkey, China and India. We discuss barriers to publications from low‐income countries.